2020
DOI: 10.3390/cancers12092443
|View full text |Cite
|
Sign up to set email alerts
|

The Regulatory Role of Mitochondrial MicroRNAs (MitomiRs) in Breast Cancer: Translational Implications Present and Future

Abstract: Breast cancer is the most prevalent and incident female neoplasm worldwide. Although survival rates have considerably improved, it is still the leading cause of cancer-related mortality in women. MicroRNAs are small non-coding RNA molecules that regulate the posttranscriptional expression of a wide variety of genes. Although it is usually located in the cytoplasm, several studies have detected a regulatory role of microRNAs in other cell compartments such as the nucleus or mitochondrion, known as “mitomiRs”. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 183 publications
(177 reference statements)
0
21
0
Order By: Relevance
“…Recent studies have found that specific miRNAs are associated with breast cancer [ 36 , 37 ]. Studies on the clinical applications of miRNAs, such as in diagnosis, prognosis, and therapeutic strategies for cancer, including breast cancer, are also gaining prominence [ 21 ]. Here, a systematic analysis of miRNA expression profiles from TCGA was performed to identify potential miRNAs for the diagnosis of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have found that specific miRNAs are associated with breast cancer [ 36 , 37 ]. Studies on the clinical applications of miRNAs, such as in diagnosis, prognosis, and therapeutic strategies for cancer, including breast cancer, are also gaining prominence [ 21 ]. Here, a systematic analysis of miRNA expression profiles from TCGA was performed to identify potential miRNAs for the diagnosis of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…They lead to the silencing of respective gene expression either by direct degradation of mRNA or inhibition of protein translation [ 11 , 12 ]; miRNAs are involved in a wide range of cancer biology processes, including regulation of target mRNA expression, which promotes tumor growth, apoptosis, progression, metastasis, and immune evasion [ 13 , 14 , 15 , 16 ]. Many studies have reported that miRNAs play key roles in the occurrence and progression of breast cancer [ 17 , 18 , 19 , 20 ]; this has prompted translational studies on miRNAs for breast cancer to be actively conducted [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned before, mitomiRs have been described as novel players in both physiologic and pathologic conditions [ 100 , 101 ]. miR-1 is responsible for protecting heart structure and functions against hypertrophy, maintaining cardiovascular health.…”
Section: Mitochondrial Mirnas—potential Contribution For Regeneratmentioning
confidence: 99%
“…Similarly, the therapeutic potential of miRNAs, namely mitochondrial ones, is promising as they have proven to be novel players in several diseases such as cancer, metabolic and neurodegenerative diseases [ 100 , 101 ]. However, firstly, the extent of mitomiRs’ regulatory effects must be assessed as well as delivery processes that allow mitomiRs to target mitochondria, minimizing off-target effects [ 141 ].…”
Section: Emerging Therapies In Regenerative Medicinementioning
confidence: 99%
“…Moreover, choice of systemic therapies such as adjuvant and neoadjuvant therapies frequently represent important procedures, depending on the lymph involvement, menopausal status, or BC subtype [ 15 ]. Among them, endocrine therapy like aromatase inhibitors (AI) or Herceptin (Trastuzumab) are prominent approaches for luminal and HER2-enriched subtypes respectively [ 16 ], whereas for aggressive TNBC tumors, immunotherapy together with novel molecular targets are being used, including microRNAs, PARP (Poly ADP-ribose polymerase), or PI3K (Phosphoinositide 3-kinases) inhibitors [ 17 , 18 , 19 ]. Thus, advances in the therapies provided for the patients, along with early diagnosis and screening, have provoked a noteworthy reduction in overall cancer mortality and cancer-specific survival during the last decades in Europe [ 20 ].…”
Section: Introductionmentioning
confidence: 99%